Community participation of patients 12 months post-stroke in Johannesburg, South Africa - Witness Mudzi; Aimee Stewart; Eustasius Musenge (AOSIS, 2013)
Background: Improvement in health-related quality of life (HRQL) is the main goal of rehabilitation. The ability of the stroke-patient to participate in various situations signifies successful rehabilitation. The aim of the study was to establish the extent of community participation and the barriers and facilitators to the participation for stroke patients after their discharge. Method: This study formed part of a larger study focusing on the impact of caregiver education on stroke survivors and their careers. This was a longitudinal study comprising 200 patients with first-time ischaemic stroke. Although the patients were followed up at home at 3 months, 6 months and 12 months post-stroke, this paper focuses on the 12-months follow-up participation results. Patient functional ability was measured by using the Barthel Index (BI) and the Rivermead Mobility Index (RMI), whereas participation was measured by using the International Classification of Functioning, Disability and Health (ICF) checklist. Descriptive statistics were used to analyse the data. Results: Patients experienced severe to complete difficulty when undertaking single and multiple tasks without help 12-months post-discharge. They struggled with the preparation of meals, household work and interpersonal interactions, and they had difficulties with community life and partaking in recreation and leisure activities. Immediate family and societal attitudes were viewed as facilitators to community participation whereas friends, transportation services and social security services were viewed as barriers to community participation. Conclusion: The patient-ability to socialise and participate in community issues is currently poor. The identified barriers to community participation need to be addressed in order to improve patient-participation in the community post-stroke.